2020
DOI: 10.21203/rs.3.rs-53950/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic Yield, Safety and Impact of Transbronchial Lung Biopsy in Mechanically Ventilated Critically Ill Patients: A Retrospective Study

Abstract: BackgroundPulmonary infiltrates of variable etiology are one of the main reasons for hypoxemic respiratory failure leading to invasive mechanical ventilation. If pulmonary infiltrates remain unexplained or progress despite treatment, the histopathological result of a lung biopsy could have significant impact on change in therapy. Surgical lung biopsy is the commonly used technique, but due to its considerable morbidity and mortality, less invasive bronchoscopic transbronchial lung biopsy (TBLB) may be a valuab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…It is worth mentioning that although all patients in this study were initially thought to have non-infectious diseases, some patients were found to have viral pneumonia. Previous studies have found similar results, regardless of the method of biopsy [3,4,25,[27][28][29]. In addition, it is also notable that four patients in our study had TBLC indicating a fibrotic phase of DAD, including two patients with a combined proliferative phase of DAD, but none of these four patients survived.…”
Section: Discussionsupporting
confidence: 82%
“…It is worth mentioning that although all patients in this study were initially thought to have non-infectious diseases, some patients were found to have viral pneumonia. Previous studies have found similar results, regardless of the method of biopsy [3,4,25,[27][28][29]. In addition, it is also notable that four patients in our study had TBLC indicating a fibrotic phase of DAD, including two patients with a combined proliferative phase of DAD, but none of these four patients survived.…”
Section: Discussionsupporting
confidence: 82%